"قائمة الوحدات المعجمية الشائعة في محتوى كتاب اللّغة العربية للسنة الأولى من التعليم المتوسط" (من النّص 22 إلى النّص42) (مجلة إحالات, 2025)
يتناول البحث إنجاز قائمة للوحدات المعجمية الشائعة في محتوى كتاب اللّغة العربية للسنة الأولى من التعليم المتوسط بنصوص محدّدة، تقوم على قاعدتين؛ الأولى: تكرار الوحدات المعجمية وشيوعها، والثانية: التفاصيل الدلالية، تهدف إلى قياس جودة الكتاب المدرسي من حيث الجودة والقبول والضعف بمنهج نقدي متعامل به على المستوى العالمي في تقييم مضمونه .Abstract : This research focuses on the development of a list of common lexical units in the Arabic language book for the third year of primary education is based on the content of two bases: the first repetition of vocabulary, the second moral change in the context, analysis of data and graphs It aims to measure the quality of the scholar book in terms of quality, acceptance and weakness with a critical approach in use at the global . level in assessing the content of the scholar book